2021
DOI: 10.3390/reports4040035
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcome in Non-Severe COVID-19: Potential Diagnostic Coagulation Tests

Abstract: COVID-19-associated coagulopathy (CAC) identifies the coagulation changes in coronavirus disease 2019 (COVID-19) and is responsible for thrombosis. CAC has been studied in critical and severe stage COVID-19 disease through tests including the D-Dimer (DD), prothrombin time (PT), thromboplastin partial time (PTT), platelet count, fibrinogen (Fib), and platelet factor 4 (PF4) tests. However, these tests have some limitations. The aim of this study was to identify more accurate warning tests for early recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Of 83 articles, 77 articles were excluded because 38 articles were duplicated, 7 did not report related data, 18 were review articles, 6 did not stratify TFPI levels according to disease severity or just reported temporal changes of TFPI levels, one was a case report, one was invitro study, one was viewpoint, four studies were without healthy controls, and the results of one study about TFPI value was correlation analysis on the reported data in Al-Tamimi et al [25] work that we had included this data in the analysis, so it was removed. Finally, with the agreement of both reviewers, six articles remained for analysis [25][26][27][28][29][30], as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 83 articles, 77 articles were excluded because 38 articles were duplicated, 7 did not report related data, 18 were review articles, 6 did not stratify TFPI levels according to disease severity or just reported temporal changes of TFPI levels, one was a case report, one was invitro study, one was viewpoint, four studies were without healthy controls, and the results of one study about TFPI value was correlation analysis on the reported data in Al-Tamimi et al [25] work that we had included this data in the analysis, so it was removed. Finally, with the agreement of both reviewers, six articles remained for analysis [25][26][27][28][29][30], as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the six studies were prospective, two were cross-sectional, and one was retrospective with a total of 684 cases and healthy controls, of whom 180 were healthy controls and 504 were COVID-19 patients with different severity (76 mild, 292 moderate, and 136 severe) (Table 1). The severity classification of COVID-19 was defined according to the WHO guidelines in three studies [26,28,29] PRISMA flow diagram demonstrating the data gathering process to finding out coronavirus disease 2019 effect on tissue factor pathway inhibitor levels. Data from [31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations